Vodnik skozi anatomsko terminologijo, Ductio per terminologiam anatomicam / Vodnič kroz anatomsku terminologiju, Ductio per terminologiam anatomicam - Pejković, Božena; Jesenšek, Marko (2026)
A Guide to Anatomical Terminology. Ductio per terminologiam anatomicam. Illustrated quadrilingual (Slovenian, Serbian, Latin and Greek) vocabulary of anatomic terms with ethymological explanation of anatomic terms that are included in the international anatomic terminology is aimed to make anatomy more  comprehensive and interesting for learning.
Keywords: human anatomy; illustrated quadrilingual terminological vocabulary; ethymology